The Effectiveness of Housing Development at Semarang Periphery to Meet the Demand for Housing - Hapsari, Intan; Dewi, Santy Paulla (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Increasing demand for housing in Semarang city simultaneously rose housing development activities. The imbalance between need and provision has caused housing backlog. Programs were conducted enabling houses be built independently by people, by government supported through national housing and by private developers. While 24.279 people do not have their own home in Semarang (Kuswartojo, 2005), 24.980 houses in Semarang were being emptied by their owners (8,5% of the total units). This indicated target inaccuracies in home ownership programs goals. Therefore it is necessary to assess the effectiveness of housing development programs by clarifying the ability to fulfill the demand, and the impact through occupancy rates. The purpose of the study is to analyze the effectiveness of housing development in Mijen district, the largest suburb regency of the Semarang city ( 16,6% of the total area). In 2000 the government developed the area into the largest housing allocation site following the downtown area. The study employed housing needs analysis dan occupancy rate analysis, both using descriptive method is reinforced with primary and secondary data.